Espaços escolares em Vila Nova de Gaia - Quatro exemplos de linguagem moderna - Diogo Alberto Barros Pereira (2017)
The main focus of the present dissertation is the network of primary schools in Vila Nova de Gaia, with special attention on four examples of Modern Architecture contained in it. Based on a self-proposed 6-month internship in the Departamento de Obras e Empreitadas da Câmara Municipal de Vila Nova de Gaia and all the concerns and questions generated by it, we propose an exercise of reflection and investigation about the School building - in its architecture and in the its importance for the territory - culminating with an interpretive analysis of four objects that are presented in this exercise as case study exemplifying a specific approach. The study is developed according to an approximation scheme. The first approach is taken to the concept of School and to the importance of the design of its spaces, followed by a historical evolution study of school spaces in Portugal followed by a second phase, the focus of the school building network in Vila Nova de Gaia, which, after a general interpretive analysis concerned in time and space which results in the approximation of four projects designed and built in a specific context: Modern Architecture.